Optimal operational conditions of PLA/PBAT mixed matrix membrane for the treatment of oily wastewater - Maryam Ghadhban; Khalid Rashid; Adnan Abdulrazak; Hicham Meskher; Yacine Benguerba; Emad Yousif Al-Sarraj; Qusay Alsalhy (Engineering and Technology Journal, 2024)
This study aims to optimize the operational variables influencing the incorporation of Hesperidin nanoparticles (HSP NPs) into poly(lactic acid)/poly(butylene adipate-co-terephthalate) (PLA/PBAT) for manufacturing mixed matrix membranes (MMMs) for oily wastewater treatment. An optimization method was employed to determine the optimal values for key process factors to achieve specific flux and rejection rates exceeding required levels. Statistical techniques such as response surface methodology (RSM) and analysis of variance (ANOVA) were used to enhance performance on a larger scale. This research investigated the impact of operating parameters on the flux and oil rejection of PLA/PBAT/HSP membranes across all samples. The variables studied included HSP NPs content (0-0.05 wt.%), oil concentration (100-300 ppm), and transmembrane pressure (1.5-3.5 bar). A mathematical model for calculating flux and rejection (%) was developed. The findings indicated that the PLA/PBAT/HSP-based MMMs demonstrated optimal efficiency, achieving a flux of 121 LMH and oil rejection of 98.53%. The optimal conditions for the HSP MMMs were 0.03 wt.% HSP, an oil concentration of 158.28 ppm, and a pressure of 3.5 bar yielded the best response. The results show that the PLA/PBAT/HSP membranes exhibited enhanced flux and separation properties, making them suitable for treating oily wastewater in various applications.